2021
DOI: 10.2500/aap.2021.42.210002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of endoscopic sinus surgery and aspirin therapy in the management of aspirin-exacerbated respiratory disease

Abstract: Background: Aspirin therapy and/or type 2 (T2) biologics are used in the management of aspirin-exacerbated respiratory disease (AERD). Objective: To identify the number of patients with AERD who tolerated aspirin therapy, yet due to persistent symptoms, incorporated T2 biologic management. Methods: A retrospective review was performed between July 2016 and June 2019. Patients with AERD and who underwent endoscopic sinus surgery (ESS), aspirin desensitization (AD), and at least 6 months of aspirin therapy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Acutely, treatments are focused on the specific organ system affected; however, to achieve long-term symptom control, a combined approach with comprehensive ESS followed by systemic treatment with aspirin desensitization (AD) and aspirin therapy after desensitization (ATAD) is usually indicated. [34][35][36] Below we review the various categories of treatment options.…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Acutely, treatments are focused on the specific organ system affected; however, to achieve long-term symptom control, a combined approach with comprehensive ESS followed by systemic treatment with aspirin desensitization (AD) and aspirin therapy after desensitization (ATAD) is usually indicated. [34][35][36] Below we review the various categories of treatment options.…”
Section: Treatmentmentioning
confidence: 99%
“…Our prior publications have shown that ESS coupled with AD and aspirin therapy after desensitization (ATAD) result in strongly favorable patient outcomes. 34,36,50 Aspirin Therapy After Desensitization Aspirin desensitization aims to build an individual's tolerance to ASA and other NSAIDs and has shown favorable outcomes in the management of patients with AERD. 51,52 .…”
Section: Endoscopic Sinus Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…The specialties that share the care of patients must work together to determine not only the treatment path that is most likely to ensure long-term health, but also to safeguard societal health care resources. For many patients with AERD, an initial "clean-out" surgery followed by sinus-directed topical corticosteroids and aspirin therapy 49,50 might lead to inexpensive long-term control, as well as remediate the dilemma of needing to avoid other NSAIDs for pain control. When this treatment approach fails patients, biologics should be considered.…”
Section: Shared Decision-makingmentioning
confidence: 99%